Local government finance in Nigeria: problems and prospects - Adedeji, Adebayo; Rowland, L. (Ile-Ife: Published for the Institute of Administration [by] University of Ife Press, 1972)
Contains a summary of the proceedings, conclusions, recommendations, and background papers of the 3d National Conference on Local Government, Benin City, Nigeria, 1970.
Includes bibliographical references and index.
lje 25/1/19
Loans
Keywords: Local finance; Local governments; Nigeria